Effect of Bian-stone hot ironing-massage and Chinese herbal medicine penetration combined with auricular acupoint sticking and pressing on relief of incomplete intestinal obstruction (砭石熨摩中药透入法联合耳穴贴压缓解不完全性肠梗阻临床症状的效果观察) - ZHANG Lihua (张丽华); XUE Li (薛丽); HUANG Yanping (黄砚萍); WANG Guifang (王贵芳) (中西医结合护理)
Objective To observe the effect of Bian-stone hot ironing-massage Chinese herbal medicine penetration combined with auricular acupoint sticking and pressing on relief of incomplete intestinal obstruction. Methods Totally 60 patients with incomplete intestinal obstruction were randomly divided into the treatment group and control group, with 30 cases in each group. All patients received symptomatic treatment and routine care, and those in the treatment group were given Bian-stone hot ironing-massage and Chinese herbal medicine penetration combined with auricular acupoint sticking and pressing. The time to relief of abdominal pain, abdominal distension and difficult defecation were observed, and the treatment efficacy was measured and compared between two groups. Results The time to relief of abdominal pain, abdominal distension, nausea and vomiting and difficult defecation in the treatment group was shorter than that in the control group (P＜0. 01). The overall effective rate was 80. 00%(24/30) in the treatment group, which was higher than 60. 00%(18/30) in the control group(P<0. 05). Conclusion The Bian-stone hot ironing-massage Chinese herbal medicine penetration combined with auricular acupoint sticking and pressing is potentially effective to relieve the clinical symptoms of incomplete intestinal obstruction and improve the therapeutic effect. (目的 观察砭石熨摩中药透入法联合耳穴贴压缓解不完全性肠梗阻临床症状的效果, 总结相关护理措施。方法 选取60例不完全性肠梗阻患者为研究对象, 随机分为治疗组和对照组, 各30例。对照组常规对症治疗, 治疗组在常规治疗基础上, 实施砭石熨摩中药透入法和耳穴贴压。观察两组腹痛、腹胀、排便等症状消失时间。结果 治疗组腹痛、腹胀、恶心或呕吐、排便减少或困难消失时间短于对照组, 差异有统计学意义(P＜0. 01)。治疗组总有效率80. 00%(24/30), 高于对照组的60. 00%(18/30), 差异有统计学意义(P＜0. 05)。结论 砭石熨摩中药透入法联合耳穴贴压兼具温经通络、理气止痛、活血通络等作用, 能有效缓解不完全性肠梗阻患者的临床症状, 提高治疗效果。)